Tenants' acceptance level of current tenancy terms for selected office buildings in Kuala Lumpur, Malaysia - Mohd Adnan, Y.; Tey, H.S. (2008)
This paper explores the common lease/tenancy agreement terms of purpose of built office buildings in Malaysia and the acceptance level of lease/tenancy agreement terms of the space occupied. It attempts to identify variation of least terms and its arrangement for office building practiced in Malaysia and other countries. In addition, the acceptance level of lease terms between local and international tenant organisations at these selected office buildings is examined. From survey findings gathered from the tenants' organisations of two selected office building chosen in the study, it can generally be concluded that both international and local organizations in the study are of the view that the clauses in the tenant/lease agreements practiced in Malaysia do not pose any major problems to them.